THE IMPACT OF TAWAKAL AND DHIKR ON MENTAL HEALTH AND STRESS IN MODERN LIFE - Isdianto, Andik; Al Indunissy, Nuruddin; Fitrianti, Novariza (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study explores the psychological fortification offered by the Islamic practices of tawakal (reliance on God) and dzikir (remembrance of God) in addressing modern challenges, such as increased anxiety due to technological advances and complex social needs. Employing a literature review methodology, this research investigates the influence of these practices on mental health and behavioral implications. The selection of peer-reviewed articles published within the last ten years involved databases like PubMed and Google Scholar with keywords related to Islamic spirituality and mental health. This method allowed a comprehensive analysis of contemporary studies, focusing on the therapeutic benefits of tawakal and dzikir in clinical settings. Results indicate that tawakal significantly reduces anxiety by fostering a relinquishing of control and instilling peace of mind, while dzikir enhances emotional stability through its meditative repetition of sacred phrases, promoting relaxation and reducing stress responses. Both practices not only support spiritual well-being but also offer practical coping mechanisms in stressful situations. The conclusion underlines the potential integration of tawakal and dzikir into conventional psychotherapeutic practices. It suggests further exploration into the incorporation of these spiritual elements within mental health frameworks to enhance therapeutic outcomes and patient recovery. This research contributes to the broader discourse on the intersection of spirituality and psychology, highlighting the relevance of traditional spiritual practices in contemporary mental health paradigms.